Creation of world poverty - Hayter, Teresa (Pluto Pr. LondonGB, 1981)
Challenges established Western views that the West through its policies fosters third world development. Argues that economic actions of the West are calculated to preserve the existing world economic order of fundamental inequality. Discusses inter alia, conventional explanations for poverty, hunger, exports of capital, trade, aid, and industrialization. Presents an alternative view to the Brandt (1980) report.